Correlation of Serum Sclerostin Levels with Carotid Intima Media Thickness in Chronic Kidney Disease Patients with Hemodialysis - Adhi Permana; Ian Effendi; Taufik Indrajaya; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Chronic kidney disease is associated with high mortality rates mainly to cardiovascular disease related with mineral and bone disorders. Sclerostin is an inhibitor of Wnt signaling which has the effect of increasing vascular calcification in patients with chronic kidney disease. There are several studies that show different results. Carotid intima media thickness ultrasound examination is a tool to identify atherosclerosis which is part of vascular calcification. The purpose of this study is to look at the correlation of sclerostin with carotid intima media thickness (CIMT) in patients with chronic kidney disease undergoing maintenance hemodialysis. In this cross-sectional study, the sclerostin concentration was measured by an enzymed linked immunosorbent assay. CIMT measurement by ultrasound mode B examination. There were 40 patients in this study. The mean sclerostin level was 256.68 ± 127.76 pg / ml. Sclerostin levels are considered high above 162 pg / ml, there are 30 people. CIMT thickening was present in 11 patients. There was no significant correlation of serum sclerostin with CIMT in patients with chronic kidney disease undergoing maintenance hemodialysis (r-0.32 p0,847). In multivariate linear regression, hemodialysis vintage is an independent factor that is significantly significant with CIMT. There was no significant correlation of serum sclerostin with CIMT in patients with chronic kidney disease undergoing hemodialysis.